A freeze/thaw stability of corned beef with carageenan - Borra, Maria Rizza Bravo ; Ma. Leonora dL. Francisco, adviser
The study was conducted to determine the freeze/thaw stability of corned beef incorporated with 0.5% kappa and 0.5% iota-carrageenan. Corned beef samples were subjected to 33 hours of freezing at -13.33°C and subsequent thawing for 33 hours at 4.44 °C. At the end of each cycle, sensory evaluation and physico-chemical analyses were conducted to evaluate the effects of the freeze/thaw conditions to the sensory and functional attributes of corned beef. A total of three freeze/thaw cycles were performed for each treatment. Results of the sensory evaluation showed that the 0.5% iota-carrageenan treatment was the most stable of the three. Most of its sensory attribute obtained the same ratings for all the freeze/thaw cycles. Incorporation of kappa and iota carrageenan generally increases the water-holding capacity of corned beef, even if it had undergone three freeze/thaw cycles, as evaluated through the two-way ANOVA. The pH of the samples, on the other hand, was only affected by the initial exposure to freezing and thawing conditions, for all treatments. Succeeding exposures to the freeze/thaw stress did not significantly affect the pH of the corned beef for all the treatments. The thaw drip for all treatments was negligible